The magnet species effect of two-leaf squill (Scilla spp.) on pollinator competition with the snowdrop (Galanthus nivalis L.) - Prokop, Pavol; Čiampor, Fedor; Bielikova, Olena; Pekárik, Ladislav; Čejka, Tomáš; Provazník, Zuzana; Mešková, Michaela; Vanerková, Viktória; Šerá, Božena; Čiamporová-Zat'ovičová, Zuzana (Frontiers in Plant Science, 2026)
IntroductionPlant-pollinator interactions may have positive, negative, or neutral influences on pollination and reproductive success of co-occurring plants. Some plants are highly attractive for pollinators (magnet species) and their presence can be beneficial for neighboring plants in terms of increased pollinator availability.MethodsCombining field and laboratory data, we examined pollinator visitation and reproductive success in early blooming co-occurring native plants, two-leaf squill (Scilla spp.) and snowdrop (Galanthus nivalis L.).ResultsThe blue flowers of Scilla significantly outcompeted the abundant white flowers of G. nivalis for pollinator visits. These differences were further supported by the higher abundance of pollinators found on G. nivalis petals (detected using eDNA metabarcoding) in experimental plots where Scilla was removed compared to plots where Scilla and G. nivalis co-occurred. eDNA analysis showed that the presence of Scilla significantly reduced alpha diversity and taxonomic richness of the G. nivalis pollinator community. Furthermore, the plot with Scilla showed a significant shift in community composition, with G. nivalis dominantly visited by taxa such as Lepidoptera, which may provide different pollination services, while the scilla-free group showed a more balanced and diverse composition including key Hymenoptera and Diptera taxa. This superior attractiveness of Scilla, consistent across both field observations and controlled lab experiments, strongly supports its role as a magnet species. Flower fertility of G. nivalis from plots with Scilla present was significantly lower than from plots without Scilla.DiscussionOverall, it appears that early flowering plant communities face strong competition for pollinators, which are scarce due to low spring temperatures. Magnet species may more significantly influence pollinator activity “in their favor” and potentially threaten the reproductive success of other, co-occurring species.